Analisis Pengaruh Produk, Harga, dan Lokasi Terhadap Keputusan Pembelian Konsumen di Mom Milk Manahan Solo - Viesti, Rizka Triziana; , Drs. Sujadi, M.M (2017)
This study aimed to analyze the effect of product, price, and location on consumer purchasing decisions at Mom Milk Manahan, Solo. The population of this study is consumers who make purchases at Milk Mom Manahan Solo. The sampling technique used in this study is simple random sampling with a sample of 100 respondents. Data collection methods used were questionnaires and interviews. Data analysis techniques in this study was to test the validity, reliability test, multiple linear regression test, test the accuracy of parameter estimators (t test), and a test of determination (R^2). The results showed that the products have a significant effect on purchasing decisions, price does not significantly influence the purchase decision, and location significantly influence purchasing decisions at Milk Mom Manahan Solo. Price does not affect to purchasing decision at Milk Mom because there are other more significant variables that influence purchasing decisions such as product and location. Therefore, consumers ignore the price of the products they consume.